2016
DOI: 10.1186/s13020-016-0096-7
|View full text |Cite
|
Sign up to set email alerts
|

Antidiabetic and antioxidant effects of catalpol extracted from Rehmannia glutinosa (Di Huang) on rat diabetes induced by streptozotocin and high-fat, high-sugar feed

Abstract: BackgroundDiabetes, associated with hyperlipidemia and oxidative stress, would lead to an increased production of reactive oxygen species. Rehmannia glutinosa (Di Huang) is widely used to nourish yin, invigorate the kidney (shen), and treat xiao ke (a diabetes-like syndrome in Chinese medicine). This study aims to investigate the antidiabetic and antioxidant effects of catalpol from R. glutinosa on rat diabetes induced by streptozotocin (STZ) and high-fat, high-sugar feed.MethodsRats (eight rats in each group … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(39 citation statements)
references
References 23 publications
1
38
0
Order By: Relevance
“…For example, recent studies by our research group have shown that various flavonoids, including actein (Choi et al, 2017), 27-deoxyactein (Suh, Choi, Jung, et al, 2018) and xanthohumol (Suh, Choi, Kim, et al, 2018), inhibit TCDD-induced toxicity in MC3T3-E1 osteoblastic cells. The beneficial effects of catalpol are primarily associated with their antioxidant activities, including the scavenging of free radicals (Zhu et al, 2016). However, to the best of our knowledge, there is no study of catalpol on TCDD toxicity in cultured osteoblastic cells.…”
Section: Discussionmentioning
confidence: 99%
“…For example, recent studies by our research group have shown that various flavonoids, including actein (Choi et al, 2017), 27-deoxyactein (Suh, Choi, Jung, et al, 2018) and xanthohumol (Suh, Choi, Kim, et al, 2018), inhibit TCDD-induced toxicity in MC3T3-E1 osteoblastic cells. The beneficial effects of catalpol are primarily associated with their antioxidant activities, including the scavenging of free radicals (Zhu et al, 2016). However, to the best of our knowledge, there is no study of catalpol on TCDD toxicity in cultured osteoblastic cells.…”
Section: Discussionmentioning
confidence: 99%
“…It is well-defined between hyperlipidemia and the development of oxidative stress, and the introduction of medicinal plants with higher antioxidant content proved effective (Tunsophon and Chootip, 2016). Previous studies indicated that a variety of plants extracts (Natal et al, 2016;Vivarelli et al, 2016;Sripradha et al, 2016), natural product (Zhu et al, 2016) and whey protein isolates (Betik et al, 2016) were used to ameliorate hyperlipidemia's laboratory animal models.…”
Section: Resultsmentioning
confidence: 99%
“…Decreased AMPK activity promotes smooth muscle cell proliferation, monocyte-to-macrophage differentiation, 37 accelerates endothelium inammation 14,38 and so on. As catalpol has been reported to play a relieving role in diabetes through regulating glucose and lipid metabolism, 39 and AMPK is a critical enzyme in energy metabolism, we posited that the protective effect of catalpol on TNF-a-treated HAECs was depending on activating AMPK. Previous studies indicated that activated AMPK could promote the accumulation of NAD + , thereby affecting SIRT1 deacetylase activity and performing variety of effects.…”
Section: Discussionmentioning
confidence: 99%
“…46,47 It was also reported that AMPK was involved in modulating endothelial cell injury in diabetes induced by NADPH oxidase overexpression. 39,48,49 By using AMPK inhibitor compound C and AMPK siRNA, we proved that catalpol enhanced AMPK activity to reduce NOX4 expression and ROS production. These ndings revealed that catalpol attenuated TNF-a induced oxidative stress partially via enhancing AMPK activity.…”
Section: Discussionmentioning
confidence: 99%